FERMENTASI ALFA AMILASE DARI ASPERGILLUS ORYZAE PADA MEDIA SAGU METROXYLON - Yetti M. Iskandar; Dine Agustine; A. Sidik; Linar Z.Udin; A. T. Karossi (Jurnal Kimia Terapan Indonesia, 1994)
Alpha amylase is an extracellular enzyme which can be obtained from Aspergillus oryzae fermentation. The production of the alpha amylase in fermentation of sago starch media (Metroxylon sp)in 600, 800 and 1500 ml scale at 30°C for 7 to 9 days in aerobic condition has been conducted. The observations at day-3 indicated that the maximum enzyme specific activity assayed at 40°C for 30 minutes incubation, was 1096 U/g protein, 963 U/g protein and 810 U/g protein for 600, 800 and 1500 ml scale respectively. At this condition starch utilization for growth reached 69% for the 600 and 800 ml scale and 71% for the 1500 ml scale and the biomass production was 6.03 g dry weight/L media, 4.03 g dry weight/L media and 5.66% g dry weight/L media for the 600, 800 and 1500 ml scale respectively.